School accountability: Incentives or sorting? - Hege Marie Gjefsen; Trude Gunnes (Statistics Norway, Research Department, 2015)
We exploit a nested school accountability reform to estimate the causal effect on teacher mobility, sorting, and student achievement. In 2003, lower-secondary schools in Oslo became accountable to the school district authority for student achievement. In 2005, information on school performance in lower secondary education also became public. Using a difference-in-difference-in-difference approach, we find a significant increase in teacher mobility and that almost all non-stayers leave the teaching sector entirely. The impact is larger on high-ability teachers following the second part of the reform. Non-stayers are largely replaced by high-ability teachers, indicating a positive sorting effect. We find a small, positive effect on student achievement after the second part of the reform, thus the mechanism in place seems to be positive teacher sorting rather than teacher incentives.
Keywords: D03; I21; J21; J38; 330; school accountability regimes; design of incentives; teacher turnover; teacher quality; teacher sorting; student achievement; difference-in-difference-in-difference